Evaluation of performance energy collection using five types of solar flat plate collector - Awang, Mariah; Mohd Basir Ruddin, Nurhanis; Abdul Rahman, Mohammad Ashraf; Hamidon, Nuramidah; Ahmad, Faridahanim; Musa, Mohd Kamaruzaman; Yusop, Fatimah; Mustafa, M. Syafiq Syazwan; Jibril, Jibril Danazimi; Abdul Rahman, Mohd Shahril (Institute of Advanced Scientific Research, 2020)
Solar radiation is emitted from the sun and collected on the surface of the earth by solar collectors. Solar energy can be transformed into useful energy in the structure of thermal power. One of the foremosteconomic always is to reapheat by exploitationsolar Flat Plate Collector (FPC). The solar collector's function is to heat water from the atmosphere. Heated water can be used for domestic and industrial uses, etc. The types of FPCs involved in this study are, for the colour’s FPC (black collector versus white collector), material’s FPC (copper collector versus polypropylene collector) and glazing’s FPC (double glazing collector versus single glazing collector) by using the Energy Solar Trainer. The present work is aimed to predict the performance of FPC tested for three different days with different types of FPC using an application of water heating The sky was almost clear with an ambient temperature in the range 20o C-36.2o C. Readings are collected from 9.00 a.m. to 5.00 p.m. with the solar radiation intensity, I = 722 W/m2 and flow rate fixed at 2 Lm-1. The result shows that the efficiency of FPCs (colour, material and glazing), the colour’s FPC, and black collector is higher than white collector. While for material’s FPC, copper collector is higher than polypropylene collector. For the glazing’s FPC, double glazing collector is higher than single collector. For the overall FPCs efficiency, double glazing collector is the highest compared to others FPC.